EFFECT OF IMPLEMENTING PROBLEM-BASED LEARNING USING SCIENTIFIC APPROACH ON ENHANCING CRITICAL THINKING - Alkamalia, Waode (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to evaluate the impact of implementing a Problem-Based Learning (PBL) model grounded in a scientific approach on enhancing students' critical thinking skills in the topic of reaction rates. The primary issue addressed is the students' limited ability to think critically when grasping abstract chemical concepts. The research employs a quasi-experimental method with a Nonequivalent Control Group Design. The population consists of eleventh-grade science students at SMA Negeri 1 Batauga, with a sample of 40 individuals selected via purposive sampling and divided into a treatment class (20 students) and a comparison class (20 students). Research instruments include essay tests to assess critical thinking skills, observation sheets for learning activities, and student response questionnaires. Data analysis involves N-gain calculations to measure score improvements, along with t-tests to identify significant differences between groups at a 0.05 significance level. Findings reveal that the average post-test score for critical thinking in the treatment class (13.55) exceeds that of the comparison class (10.30). The average N-gain value for the treatment class is 0.28, surpassing the comparison class's 0.20, though both fall into the low category. The t-test yields a t-calculated = 2.230 > t-table = 2.024, indicating a significant difference between the groups. Furthermore, student activities during the science-based PBL instruction reached an outstanding category (82%), and student responses achieved an average score of 2.96 in the good category.